The role of female farmers in improving family welfare in South Bali Sadhar Village Banjit District Way Kanan Regency, Lampung - Rangga, Kordiyana K; Syarif, Yuniar Aviati; Ibnu, Muhammad; Widiastri, Ni Luh Kadek (Universitas Islam Negeri Ar-Raniry, 2023)
This study aims at contructingthe role of female farmers in improving family welfare. The research was carried out in March 2022-April 2022 in South Bali Sadhar Village, Banjit District, Way Kanan Regency. Lampung. Indonesia. The informants in this study were female farmers and male farmers who worked in the lowland rice sector with a total of 12 people, consisted of 6 women and 6 men. The approach used in this study is a qualitative approach with case studies method. Data analysis used in this study is reduce data, data colection, data presentation and conclusions drawing. The results of this study indicate that the role of female farmers in the village of South Bali Sadharin improving family welfare is divided into three parts are reproductive role, productive role and social role. The reproductive role as housewives, the productive role as lowland rice farmers and as farm laborers. These activities include preparation of production facilities, seeding, planting, maintenance, harvesting and post-harvest. The social role is as a member of the community in both general and religious activities. The involvement of women in these three types of roles can help improve family welfare, for example women helping their husbands earn a living as lowland rice farmers so that family needs can be gradually met